Place Names in Ekegusii Language: A Cognitive Linguistics Approach (Universitas Negeri Semarang, 2021)
This paper analyses place names in the Ekegusii language from the cognitive linguistics point of view. The study is grounded on three objectives: to identify and explain the Ekegusii names of places, to describe the social cultural values, and to account for the cognitive processes involved in their mapping, analysis and elucidation. The data comprises of a list of Ekegusii place names collected from two counties, Kisii and Nyamira, by interviewing people through snowballing, and later holding a panel discussion with selected elders regarding the mapping processes and meanings associated with them. The Cognitive Metaphor Theory was used to map them to the different types of conceptual domains. Findings from this study show that place names in Ekegusii are conceptualized as seasons, topography, people, animals, plants and objects (as source domains which are social-culturally determined), and portray their cultural identity and tradition. The study concludes by suggesting further research in onomastics, especially on metaphor and metonymy in other languages of the world.